Polycaprolactam composite material as well as preparation method and application thereof
By preparing a carbon quantum dot solution through electrolytic graphite and mixing it with caprolactam for ring-opening polymerization, the problem of poor antibacterial performance of polycaprolactam materials is solved, and the antifungal and far-infrared properties are improved, making it suitable for applications in the field of big health.
Patent Information
- Application Number
- CN202410369507.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2025-09-30
AI Technical Summary
The antibacterial properties of existing polycaprolactam materials are poor, making it difficult to meet the needs of functional enhancement and differentiated production.
A carbon quantum dot solution is prepared by electrolytically forming a graphite body, and after mixing with caprolactam, a ring-opening and polymerization reaction is carried out under closed conditions to prepare a polycaprolactam composite material. The filtering and drying steps of the carbon quantum dots are omitted, and a composite material with excellent antibacterial properties is directly obtained.
The prepared polycaprolactam composite material exhibits excellent antibacterial properties, especially antifungal and far-infrared properties, which enhances the added value of the material.
Smart Images

Figure BDA0004765087730000091 
Figure BDA0004765087730000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of polycaprolactam, and in particular to a polycaprolactam composite material and a preparation method and application thereof. Background Art
[0002] Polycaprolactam (such as polyamide 6) is the product with the largest output and the widest application among polycaprolactam engineering plastics. It has good comprehensive performance and high cost-effectiveness, and can be used in many fields such as the automotive industry, electrical industry, machinery industry, and civilian living materials. As people's needs for product functions become increasingly personalized, various functional polycaprolactams are emerging in an endless stream. Antibacterial properties and far-infrared properties have been important research directions for functional polycaprolactam in recent years, and are widely used in the field of big health. Polycaprolactam nanocomposites can greatly improve many properties of polycaprolactam, such as thermal properties, mechanical properties, flame retardancy and barrier properties, thereby increasing the added value of polycaprolactam nanocomposites, which is also an important development direction of polycaprolactam materials today.
[0003] However, the antibacterial and other properties of existing polycaprolactam are not good, and functional enhancement is needed to achieve differentiated and differentiated production. Summary of the Invention
[0004] The purpose of the present disclosure is to provide a polycaprolactam composite material and a preparation method and application thereof. The method disclosed in the present disclosure is simple and easy to implement, and the prepared polycaprolactam composite material has excellent antibacterial properties.
[0005] In order to achieve the above objectives, the present disclosure provides a first aspect of a method for preparing a polycaprolactam composite material, the method comprising:
[0006] S1, connecting the graphite molded body to the positive electrode of a DC power supply, connecting the conductor to the negative electrode of the DC power supply, and electrolyzing in an electrolyte at 5-20 V for 1-10 days to obtain a solution containing carbon quantum dots, wherein the particle size of the carbon quantum dots is 2-10 nm;
[0007] S2. mixing caprolactam with the solution containing carbon quantum dots to obtain a mixed solution; the weight ratio of the caprolactam to the solution containing carbon quantum dots is 1000:(0.001-0.2), and the solution containing carbon quantum dots is calculated as carbon quantum dots;
[0008] S3. Under closed conditions, the mixed solution is subjected to a ring-opening reaction and a polymerization reaction in sequence.
[0009] Optionally, in step S1, based on the total number of carbon quantum dots, the content of carbon quantum dots with a particle size of 3-8 nm is 60-100%, preferably 80-100%, and more preferably 90-100%.
[0010] Optionally, in step S2, the mixing conditions include: temperature of 75-120°C, pressure of 0-0.5 MPa, time of 10-300 min, stirring rate of 100-1000 rpm; the weight ratio of the caprolactam to the carbon quantum dot solution is 1000:(0.005-0.15).
[0011] Optionally, step S3 comprises: performing the ring-opening reaction on the mixed solution at 120-280° C. and 0-0.5 MPa for 1-10 hours under an inert atmosphere and stirring conditions, removing water in the ring-opening reaction system to obtain a ring-opening mixed product;
[0012] The ring-opening mixed product is subjected to polymerization reaction at 220-300° C. and a vacuum degree of 0.001-0.1 MPa for 1-10 hours to obtain a polymer melt.
[0013] Optionally, in step S3, the conditions for the ring-opening reaction include: temperature of 200-240° C., time of 2-6 hours, and pressure of 0.1-0.5 MPa;
[0014] The polymerization reaction conditions include: temperature of 220-260° C., time of 1-8 hours, and vacuum degree of 0.002-0.05 MPa.
[0015] Optionally, step S3 includes sequentially extruding, cooling, pelletizing and extracting the polymer melt obtained by the polymerization reaction to obtain a polycaprolactam composite material.
[0016] Optionally, in step S1, the content of carbon quantum dots in the carbon quantum dot-containing solution is 0.01-2 weight ‰, and the particle size of the carbon quantum dots is 3-8 nm;
[0017] The electrolysis conditions include: voltage of 8-15V, time of 3-8 days, and temperature of 0-80°C;
[0018] The electrolyte is water, an organic acid solution, an inorganic acid solution, or a solution containing an organic acid and an inorganic acid;
[0019] The carbon content of the graphite molded body is greater than 99 wt % and the ash content is less than 1 wt %. Preferably, the carbon content is greater than 99.9 wt % and the ash content is less than 0.1 wt %.
[0020] A second aspect of the present disclosure provides a polycaprolactam composite material prepared by the method provided by the first aspect of the present disclosure.
[0021] Optionally, the polycaprolactam composite material has a fungus inhibition rate of 80-99%, a far-infrared emissivity of 0.80-0.95, and a fiber tensile breaking strength greater than 3.5 cN / dtex.
[0022] The third aspect of the present disclosure provides an application of the polycaprolactam composite material provided in the second aspect of the present disclosure in the antifungal field.
[0023] Through the above technical solution, the method disclosed in the present invention is simple and easy to implement, and the prepared polycaprolactam composite material has excellent antibacterial properties, especially antifungal properties.
[0024] Other features and advantages of the present disclosure will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0025] The following describes the specific embodiments of the present disclosure in detail. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure and are not intended to limit the present disclosure.
[0026] A first aspect of the present disclosure provides a method for preparing a polycaprolactam composite material, the method comprising:
[0027] S1, connecting the graphite molded body to the positive electrode of a DC power supply, connecting the conductor to the negative electrode of the DC power supply, and electrolyzing in an electrolyte at 5-20 V for 1-10 days to obtain a solution containing carbon quantum dots, wherein the particle size of the carbon quantum dots is 2-10 nm;
[0028] S2. mixing caprolactam with the solution containing carbon quantum dots to obtain a mixed solution; the weight ratio of the caprolactam to the solution containing carbon quantum dots is 1000:(0.001-0.2), and the solution containing carbon quantum dots is calculated as carbon quantum dots;
[0029] S3. Under closed conditions, the mixed solution is subjected to a ring-opening reaction and a polymerization reaction in sequence.
[0030] The method disclosed herein uses a solution containing carbon quantum dots prepared by electrolysis as a raw material, mixes it with caprolactam at a specific dosage ratio, and conducts a ring-opening polymerization reaction under airtight conditions to prepare a polycaprolactam composite material. Compared with the existing technology, the solution containing carbon quantum dots obtained by electrolysis is directly used for the ring-opening polymerization of caprolactam at a specific low dosage, eliminating the steps of filtering and drying the carbon quantum dots, and directly obtaining a functional polycaprolactam composite material. This method is simple and easy to implement, and the prepared polycaprolactam composite material has superior antibacterial properties, especially antifungal properties, far-infrared properties, and structural strengthening properties.
[0031] In the present disclosure, the particle size of carbon quantum dots in a solution containing carbon quantum dots can be analyzed by using a transmission microscope to analyze the solution containing carbon quantum dots. Any 100 carbon quantum dot particles in the field of view are taken, and the particle sizes of the carbon quantum dot particles are counted respectively. The particle size range of the 100 carbon quantum dot particles obtained by counting is used as the particle size range of the carbon quantum dots in the solution containing carbon quantum dots.
[0032] In a specific embodiment of the present disclosure, in step S1, based on the total number of carbon quantum dots, the content of carbon quantum dots with a particle size of 3-8 nm is 60-100%, preferably 80-100%, and more preferably 90-100%. In the present disclosure, the content of carbon quantum dots with a particle size of 3-8 nm can be measured by the following method: a solution containing carbon quantum dots is subjected to transmission electron microscopy analysis, 100 carbon quantum dot particles are randomly selected within the field of view, and the particle sizes of the carbon quantum dot particles are respectively counted, and the proportion of the number of carbon quantum dots with a particle size of 3-8 nm to the total number of particles is calculated.
[0033] According to the present disclosure, the polymerization reaction can be carried out in an apparatus conventionally used in the art, for example, a high-pressure reactor with a feed port and a vent. In a specific embodiment of the present disclosure, in step S2, the mixing conditions include: a temperature of 75-120°C, a pressure of 0-0.5 MPa, a time of 10-300 min, and a stirring rate of 100-1000 rpm. Preferably, the temperature is 80-90°C, the pressure is 0.1-0.3 MPa, the time is 30-240 min, and the stirring rate is 300-800 rpm.
[0034] In a preferred embodiment of the present disclosure, in step S2, the weight ratio of the caprolactam to the carbon quantum dot-containing solution is 1000:(0.005-0.15), preferably 1000:(0.01-0.05).
[0035] In a specific embodiment of the present disclosure, step S3 includes: under an inert atmosphere and stirring conditions, subjecting the mixed solution to the ring-opening reaction at 120-280°C and 0-0.5MPa for 1-10 hours, removing the water in the ring-opening reaction system, and obtaining a ring-opening mixed product; subjecting the ring-opening mixed product to the polymerization reaction at 220-300°C and a vacuum degree of 0.001-0.1MPa for 1-10 hours to obtain a polymer melt. In the present disclosure, the inert atmosphere contains inert gases such as nitrogen and argon. The present disclosure does not impose any specific restrictions on the stirring rate in step S3, as long as it can uniformly mix the reactants, for example, it can be 200-1200rpm. The water in the ring-opening reaction system in the present disclosure includes the water obtained by the ring-opening reaction and the water in the solution containing carbon quantum dots used in the ring-opening reaction. The water in the ring-opening reaction system can be removed by conventional means in the art, for example, by releasing steam from the exhaust hole of the reactor.
[0036] In a specific embodiment of the present disclosure, in step S3, the conditions for the ring-opening reaction include: temperature of 200-240°C, time of 2-6 hours, and pressure of 0.1-0.5 MPa; the conditions for the polymerization reaction include: temperature of 220-260°C, time of 1-8 hours, and vacuum degree of 0.002-0.05 MPa.
[0037] In a specific embodiment of the present disclosure, step S3 comprises: sequentially extruding, cooling, pelletizing and extracting the polymer melt obtained by the polymerization reaction to obtain a polycaprolactam composite material.
[0038] In a specific embodiment of the present disclosure, in step S1, the content of carbon quantum dots in the carbon quantum dot-containing solution is 0.01-2 weight ‰, preferably 0.05-1 weight ‰, and the particle size of the carbon quantum dots is 3-8 nm, preferably 4-6 nm. The particle size of the carbon quantum dots in the present disclosure can be obtained by transmission electron microscopy. When the composition of the solution containing carbon quantum dots is within the above range, the prepared polycaprolactam composite material has better antibacterial properties.
[0039] According to the present disclosure, the particle size and particle size distribution of carbon quantum dots can be controlled by changing the electrolysis conditions. In one embodiment, the electrolysis conditions may include: a voltage of 8-15V, a time of 3-8 days, and a temperature of 0-80°C; the electrolyte is water, an organic acid solution, an inorganic acid solution, or a solution containing an organic acid and an inorganic acid; wherein the organic acid may include, but is not limited to, common organic acids such as formic acid, acetic acid, cinnamic acid, citric acid, citric acid, ascorbic acid, and tartaric acid, and the inorganic acid may include, but is not limited to, common inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, sulfurous acid, carbonic acid, hydrobromic acid, and hydroiodic acid. The carbon content of the graphite molded body is greater than 99% by weight and the ash content is less than 1% by weight; preferably, the carbon content is greater than 99.9% by weight and the ash content is less than 0.1% by weight. The present disclosure does not impose any specific restrictions on the shape and source of the graphite molded body, as long as the carbon quantum dots of the particle size required by the present disclosure can be obtained by electrolysis. For example, the graphite molded body may be a graphite rod or a graphite sheet.
[0040] According to the present disclosure, the conductive body connected to the negative electrode of the power supply can be any conductive shaped body, such as a copper rod, copper plate, copper wire, a platinum rod, platinum plate, platinum wire, etc., or a graphite shaped body. The graphite shaped body connected to the negative electrode of the power supply can be the same as or different from the graphite shaped body connected to the positive electrode of the power supply, but is preferably the same.
[0041] The second aspect of the present disclosure provides a polycaprolactam composite material prepared by the method provided in the first aspect of the present disclosure. The polycaprolactam composite material disclosed in the present disclosure has excellent antibacterial properties.
[0042] In a specific embodiment of the present disclosure, the polycaprolactam composite material has excellent antibacterial properties, especially antifungal properties.
[0043] In a specific embodiment of the present disclosure, the polycaprolactam composite material has a fungal inhibition rate of 80-99%, a far-infrared emissivity of 0.80-0.95, and a fiber tensile breaking strength greater than 3.5 cN / dtex.
[0044] The third aspect of the present disclosure provides an application of the polycaprolactam composite material provided in the second aspect of the present disclosure in the antifungal field.
[0045] The polycaprolactam composite material disclosed herein has excellent antifungal properties and can be used as a masterbatch for plastics, films, and fiber-based materials. It is more conducive to application in the field of health, such as the preparation of physical therapy clothing, underwear, blankets, bedding, tents, various product panels, packaging materials, facial masks, wet wipes, etc.
[0046] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.
[0047] In the following examples, the material characterization and performance involved were obtained by testing using the following methods:
[0048] (1) Particle size measurement of carbon quantum dots in a solution containing carbon quantum dots
[0049] A transmission electron microscope (JEOL, Japan Electronics Co., Ltd., JEM-2100F) was used for the measurement. The test conditions were as follows: an accelerating voltage of 20 kV, a suspension method for sample preparation, an appropriate amount of carbon quantum dot solution was placed in a 2 mL glass bottle, dispersed with anhydrous ethanol, and shaken evenly. The sample was dropped onto a sample net with a diameter of 3 mm using a dropper. After drying, it was placed in a sample injector and then inserted into the corresponding position of the electron microscope for observation. 100 particles were randomly selected for particle size statistics.
[0050] (2) Determination of concentration of solution containing carbon quantum dots
[0051] The drying method was used to determine the carbon quantum dots. Specifically, a certain amount of carbon quantum dot solution (M0) was vacuum filtered and then placed in a vacuum drying oven at 100°C for 24 h to obtain the dried carbon quantum dots (M d ), and the carbon quantum dot content C is calculated according to formula (1).
[0052] C%=M d / M0×100…………Formula (1).
[0053] Example 1
[0054] S1. At room temperature and pressure, add 110L of distilled water and 25g of citric acid to a PP water tank (1m*0.12m*1m) and mix evenly. After the citric acid is dissolved, connect the positive and negative electrodes of a DC power supply to the two ends of a 60cm*60cm*5mm graphite plate and place it vertically therein. Under stirring conditions, adjust the voltage to 10V and then perform the electrolysis reaction. After 5 days, a solution containing carbon quantum dots is obtained. After membrane separation, a carbon quantum dot aqueous solution with a particle size of 2-10nm is obtained. After measurement, based on the total number of carbon quantum dots after separation, the content of carbon quantum dots with a particle size of 3-8nm is 100%, and the content of carbon quantum dots in the carbon quantum dot-containing solution is 0.15‰.
[0055] S2. In a 50 L polymerization reactor, 5 kg of a solution containing carbon quantum dots and 20 kg of caprolactam were stirred at 83° C. and normal pressure for 15 min to form a mixed solution at a stirring speed of 500 rpm.
[0056] S3. Under a nitrogen atmosphere and autogenous pressure, the mixed solution is heated to 205°C and 0.2 MPa for a ring-opening reaction for 5 hours, while automatically draining when the pressure exceeds 0.3 MPa. The pressure is released and the mixture is evacuated to 0.002 MPa. The dispersion is heated to 260°C in a polymerization reactor and reacted for 6 hours to obtain a polycaprolactam composite polymer melt. The polycaprolactam composite polymer melt is extruded, pelletized, water-cooled, extracted, and dried to obtain a polycaprolactam composite material.
[0057] Example 2
[0058] The polycaprolactam composite material was prepared by the same method as in Example 1, except that in step S2, 20 kg of the solution containing carbon quantum dots was added to obtain a mixed solution.
[0059] Example 3
[0060] The polycaprolactam composite material was prepared by the same method as in Example 1, except that in step S2, the amount of the solution containing carbon quantum dots added was 0.25 kg to obtain a mixed solution.
[0061] Example 4
[0062] A polycaprolactam composite material was prepared using the same method as in Example 1, except that in step S1, electrolysis was performed in an electrolyte at 7 V for 10 days to obtain a solution containing carbon quantum dots, which was then subjected to membrane separation to obtain an aqueous solution of carbon quantum dots with a particle size of 2-10 nm. Measurements showed that, based on the total number of carbon quantum dots after separation, the content of carbon quantum dots with a particle size of 3-8 nm was 85%, and the concentration of the carbon quantum dot-containing solution was 0.08‰.
[0063] Example 5
[0064] The polycaprolactam composite material was prepared by the same method as in Example 1, except that in step S2, the mixing temperature was 60° C., the pressure was 0.55 MPa, the time was 10 min, and the stirring rate was 90 rpm.
[0065] Example 6
[0066] The polycaprolactam composite material was prepared by the same method as in Example 1, except that in step S3, the temperature of the ring-opening reaction was 170°C, the time was 1 hour, and the pressure was 0.08 MPa; the temperature of the polymerization reaction was 300°C, the time was 5 hours, and the vacuum degree was 0.001 MPa.
[0067] Comparative Example 1
[0068] The polycaprolactam composite material was prepared by the same method as in Example 1, except that step S1 was not performed and an equal amount of deionized water was used instead of the carbon quantum dot solution in step S2.
[0069] Comparative Example 2
[0070] The polycaprolactam composite material was prepared by the same method as in Example 2, except that step S1 was not performed and an equal amount of deionized water was used instead of the carbon quantum dot solution in step S2.
[0071] Comparative Example 3
[0072] The polycaprolactam composite material was prepared by the same method as in Example 3, except that step S1 was not performed and an equal amount of deionized water was used instead of the carbon quantum dot solution in step S2.
[0073] Comparative Example 4
[0074] The polycaprolactam composite material was prepared by the same method as in Example 1, except that in step S2, a graphene aqueous dispersion (average particle size 3 μm) of equal weight and concentration was used instead of the carbon quantum dot solution in Example 1.
[0075] Comparative Example 5
[0076] The polycaprolactam composite material was prepared by the same method as in Example 1, except that in step S2, the weight ratio of caprolactam to the carbon quantum dot-containing solution was 1000:0.5.
[0077] Comparative Example 6
[0078] A polycaprolactam composite material was prepared by the same method as in Example 1, except that, in step S1, 5 parts of o-phenylenediamine were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an o-phenylenediamine solution, and 3 parts of acetic acid were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an acid solution. The o-phenylenediamine solution and the acid solution were mixed and added to a stainless steel autoclave, and reacted at 160°C for 12 hours to obtain a dark brown solution. The resulting product was washed with deionized water and anhydrous ethanol, centrifuged, and finally dried to obtain nitrogen-doped carbon quantum dots (N-CQDs). In step S3, an equal amount of nitrogen-doped carbon quantum dots (N-CQDs) was used instead of the carbon quantum dot solution.
[0079] Test Case
[0080] The antifungal properties, far-infrared properties and structural strengthening properties of the polycaprolactam composite materials prepared in the above examples and comparative examples were tested respectively. The specific testing methods are as follows. The specific results are shown in Table 1.
[0081] (1) Antifungal properties were tested using GB / T 20944.3-2008.
[0082] (2) The far infrared emissivity is obtained by testing using GB / T30127-2013.
[0083] (3) Fiber tensile strength is measured according to GB / T 14344-2008.
[0084] Table 1
[0085]
[0086]
[0087] It can be seen from the above that the polycaprolactam composite material prepared by the method of the present disclosure, especially under preferred conditions, has better antibacterial properties, far-infrared emission properties and fiber tensile breaking strength.
[0088] The preferred embodiments of the present disclosure are described in detail above. However, the present disclosure is not limited to the specific details of the above embodiments. Within the technical concept of the present disclosure, various simple modifications can be made to the technical solutions of the present disclosure, and these simple modifications all fall within the scope of protection of the present disclosure.
[0089] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any appropriate manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0090] In addition, the various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing a polycaprolactam composite material, the method comprising: S1, connecting the graphite molded body to the positive electrode of a DC power supply, connecting the conductor to the negative electrode of the DC power supply, and electrolyzing in an electrolyte at 5-20 V for 1-10 days to obtain a solution containing carbon quantum dots, wherein the particle size of the carbon quantum dots is 2-10 nm; S2. mixing caprolactam with the solution containing carbon quantum dots to obtain a mixed solution; the weight ratio of the caprolactam to the solution containing carbon quantum dots is 1000:(0.001-0.2), and the solution containing carbon quantum dots is calculated as carbon quantum dots; S3. Under closed conditions, the mixed solution is subjected to a ring-opening reaction and a polymerization reaction in sequence.
2. The method according to claim 1, wherein In step S1, based on the total number of carbon quantum dots, the content of carbon quantum dots with a particle size of 3-8 nm is 60-100%, preferably 80-100%, and more preferably 90-100%.
3. The method according to claim 1, wherein In step S2, the mixing conditions include: temperature of 75-120°C, pressure of 0-0.5 MPa, time of 10-300 min, and stirring rate of 100-1000 rpm; The weight ratio of the caprolactam to the carbon quantum dot-containing solution is 1000:(0.005-0.15).
4. The method according to claim 1, wherein Step S3 comprises: performing the ring-opening reaction of the mixed solution at 120-280° C. and 0-0.5 MPa for 1-10 hours under an inert atmosphere and stirring conditions, removing water in the ring-opening reaction system to obtain a ring-opening mixed product; The ring-opening mixed product is subjected to polymerization reaction at 220-300° C. and a vacuum degree of 0.001-0.1 MPa for 1-10 hours to obtain a polymer melt.
5. The method according to claim 4, wherein: In step S3, the ring-opening reaction conditions include: temperature of 200-240° C., time of 2-6 hours, and pressure of 0.1-0.5 MPa; The polymerization reaction conditions include: temperature of 220-260° C., time of 1-8 hours, and vacuum degree of 0.002-0.05 MPa.
6. The method according to claim 1, wherein Step S3 comprises: sequentially extruding, cooling, pelletizing and extracting the polymer melt obtained by the polymerization reaction to obtain a polycaprolactam composite material.
7. The method according to claim 1, wherein In step S1, the content of carbon quantum dots in the carbon quantum dot-containing solution is 0.01-2 wt‰, and the particle size of the carbon quantum dots is 3-8 nm; The electrolysis conditions include: voltage of 8-15V, time of 3-8 days, and temperature of 0-80°C; The electrolyte is water, an organic acid solution, an inorganic acid solution, or a solution containing an organic acid and an inorganic acid; The carbon content of the graphite molded body is greater than 99 wt % and the ash content is less than 1 wt %. Preferably, the carbon content is greater than 99.9 wt % and the ash content is less than 0.1 wt %.
8. The polycaprolactam composite material prepared according to any one of claims 1 to 7.
9. The polycaprolactam composite material according to claim 8, wherein The polycaprolactam composite material has a fungus inhibition rate of 80-99%, a far-infrared emissivity of 0.80-0.95, and a fiber tensile breaking strength greater than 3.5 cN / dtex.
10. Use of the polycaprolactam composite material according to claim 8 or 9 in the antifungal field.